Robust speaker identification based on selective use of feature vectors - Kwon, Soonil; Narayanan, Shrikanth (ELSEVIER, 2007)
A new method for speaker identification that selectively uses feature vectors for robust decision-making is described. Experimental results, with short speech segments ranging from 0.25 to 2 s, showed that our method consistently outperforms other approaches yielding relative improvements of 20-51% and 15-30% over baseline GMM and the LDA-GMM systems, respectively. (c) 2006 Elsevier B.V. All rights reserved.